High level expression of Saccharomyces cerevisiae chitinase (ScCTS1) in Pichia pastoris for degrading chitin - Youxi, Zhao; Huihui, Jiang; Zhiming, Rao; Yizhi, Ji; Yanling, Cheng; Yanhe, Ma (International Journal of Agricultural and Biological Engineering, 2015)
Chitin is the second most abundant renewable biopolymer in the world. Chitinases play important roles in the degradation of chitin. Chitinases are produced by different organisms for different purposes, which are widely expressed in the three domains of life, ranging from archaea, bacteria, to fungi, yeasts, plants, insects, and even vertebrates. But there are few reports about Saccharomyces cerevisiae chitinase (ScCTS1). The aim of this study was to realize the high level expression of ScCTS1. The ScCTS1 was cloned into the expression vector pPIC9K. The recombinant plasmid was linearized and transformed into competent Pichia pastoris GS115. After screening by G418 plate, the fermentation conditions were optimized. Ultimately, under the optimal fermentation conditions, ScCTS1 enzymatic activity reached up to 94.6 U/mL. This paper presents the first report on the heterologous expression of a full-length ScCTS1 with considerably high activity. The work will not only make a great stride towards its potential applications in biotechnology, but also facilitate elucidating the precise mechanism of yeast cell division.Keywords: chitinases, heterologous expression, Saccharomyces cerevisiae, pichia pastoris, biotechnologyDOI: 10.3965/j.ijabe.20150805.2071Citation: Zhao Y X, Jiang H H, Rao Z M, Ji Y Z, Cheng Y L, Ma Y H. High level expression of Saccharomyces cerevisiae chitinase (ScCTS1) in Pichia pastoris for degrading chitin. Int J Agric & Biol Eng, 2015; 8(5): 142－150.